Evaluating the Waste Prevention Potential of a Multi- versus Single-Use Surgical Stapler - Meissner M; Lichtnegger S; Gibson S; Saunders R (Dove Medical Press, 2021)
Markus Meissner,1 Sabrina Lichtnegger,1 Scott Gibson,2 Rhodri Saunders2 1Austrian Institute of Ecology, Vienna, Austria; 2Coreva Scientific GmbH & Co KG, Koenigswinter, GermanyCorrespondence: Rhodri SaundersCoreva Scientific GmbH & Co KG, Koenigswinter, GermanyTel +49 2223 781 8010Fax +49 761 76 999 421Email rhodri@coreva-scientific.comPurpose: Within the hospital, surgery is recognized as a resource-intensive activity that disproportionately generates large volumes of healthcare waste. Single-use, disposable medical supplies contribute substantially to this problem, and more broadly to the depletion of scarce resources. Given that many surgical procedures utilize surgical stapling techniques, this study uses surgical stapling systems as functional units for evaluating the waste prevention potential of switching from single-use systems (SUSs) to multi-use systems (MUSs).Materials and Methods: Two frequently used surgical stapling systems, Ethicon's SUS: ECHELON FLEX™ and Medtronic's MUS: Signia™ Stapling Technology, were mechanically deconstructed to their individual raw material components to calculate the composition of each system. Total waste as well as extended resource use (the total material requirement [TMR]) were then calculated for three different surgical procedures; laparoscopic sleeve gastrectomy, laparoscopic gastric bypass, and video-assisted thoracoscopic (VATS) lobectomy. The differences in outcomes for SUSs versus MUSs were then calculated.Results: For each surgical procedure considered, switching from a SUS to a MUS led to a reduction in total waste accumulated per procedure and TMR. Reductions in waste were 40% (sleeve gastrectomy), 70% (gastric bypass), and 62% (VATS lobectomy). The TMR reductions were higher, at 92% (sleeve gastrectomy), 96% (gastric bypass), and 95% (VATS lobectomy). Both waste and TMR reduction were realized with the MUS system as long as the reusable parts were used more than four times. This was true for all analyzed surgical procedures.Conclusion: Switching from a SUS to MUS facilitates a reduction in total surgical waste and TMR for sleeve gastrectomy, gastric bypass, and VATS lobectomy surgical procedures.Keywords: circular economy, reuse, resource efficiency, hospital costs, operating room, healthcare economics